Evaluation method for hot rolling & run out table cooling parameters. Issue 17 (22nd November 2021) - Taylor, T.; Sugiyama, S.; Ishikawa, A.; Wang, H.; Yanagimoto, J.
Abstract : A new hot rolling & Run Out Table cooling simulator is constructed. The simulator permits continuous collation of process data including in-situ temperature measurement at numerous positions of the strip steel. Tensile properties and microstructural analysis of the hot rolled strip are correlated to the collated process data. A numerical model including phase transformation and latent heat evolution is constructed and calibrated against the experimental data. The resulting numerical model can be used to efficiently predict the optimal process parameters for manufacturing hot rolled strip steels, while the new hot rolling & Run Out Table cooling simulator can be used to efficiently validate the numerical simulation results before up-scaling to the industrial hot mill.